Correction: Synthesis and characterisation of brannerite compositions (U0.9Ce0.1)1−xMxTi2O6 (M = Gd3+, Ca2+) for the immobilisation of MOX residues. Issue 6 (19th January 2021) - Bailey, D. J.; Stennett, M. C.; Ravel, B.; Grolimund, D.; Hyatt, N. C.
Abstract : Correction for 'Synthesis and characterisation of brannerite compositions (U0.9 Ce0.1 )1− x M x Ti2 O6 (M = Gd 3+, Ca 2+ ) for the immobilisation of MOX residues' by D. J. Bailey et al ., RSC Adv., 2018, 8, 2092–2099. DOI: ; 10.1039/C7RA11742F .